THE POSITION OF THE RUSSIAN GOVERNMENT TO THE ANGLO-BUR WAR - Sattorov Nurbek Abdurazzoqovich (Research Parks Publishers, 2020)
After the Republic of Uzbekistan gained its independence, there were great opportunities for changes in the political, socio-economic, cultural and educational life of the country. Under the leadership of the leadership of the republic, including President Mirziyoev Sh. He said,